How Free Is Free Health Care? An Assessment of Universal Health Coverage Among Jamaicans with Sickle Cell Disease (Mary Ann Liebert, 2021)
Purpose: In an effort to transition toward universal health coverage (UHC), Jamaica abolished user fees at all public health facilities in 2008. We aimed to determine the extent of out-of-pocket payments (OPPs) and the other cost barriers to UHC among patients with sickle cell disease (SCD). Methods: Patients presenting to the Sickle Cell Unit in Kingston, Jamaica, for routine care between October 2019 and August 2020 were consecutively recruited and interviewed about their latest hospitalization within the previous 4 weeks. Parents or guardians completed the questionnaire on behalf of pediatric patients. The questionnaire included the Patient Satisfaction Questionnaire Short Form (PSQ)-18 and the health module of the Jamaica Survey of Living Conditions. Results: There were 103 patients with ages ranging from 7 months to 56 years (51.5% female, 60.2% public hospitalizations, and 54.4% pediatric). The modal income (J$6200?$11,999 per week) was similar to the minimum wage and 48.5% lived in overcrowded households. Government drug-subsidy cards were owned by 39.8%. OPPs were made by 19.4% of persons for items and tests that were unavailable at public facilities. There were no costs reported by 69.6%, who visited public pharmacies. Similarly, the cost of admission to public hospitals was free for 95.4% of subjects. Using public transportation, private hospitalization, and having more disease complications were predictive of a perception that health care is unaffordable. Conclusion: Most SCD subjects reported no expense with public hospitalizations; however, approximately one in five reported OPPs. Efforts are needed to increase the availability of subsidized items, and the use of drug-subsidy cards, to improve UHC.